Pengembangan Media LKPD Berbasis Self-Regulation untuk Siswa Sekolah Dasar - Putri, Sofi Andini Julia; Istiq’faroh, Nurul; Rahma, Echa Yulia (Innovations in Multidisciplinary Education Journal, 2026)
Self-regulation skills are a crucial component of independent learning for elementary school students, yet many students still face difficulties in managing emotions when encountering academic challenges. This research aims to develop and test the feasibility of a self-regulation-based Student Worksheet (LKPD) utilizing the Independent Emotion Regulation (REM) strategy for fifth-grade elementary school students. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate), limited to the Develop stage. Data were collected through practitioner expert validation instruments and student response questionnaires. The results indicated that the "I Can Manage My Emotions" LKPD media achieved a validation score of 91.6%, categorized as "Very Valid." Furthermore, the practicality test through student responses reached a score of 90%, categorized as "Very Practical." These findings suggest that the integration of the REM strategy within the LKPD effectively provides students with the autonomy to choose appropriate self-calming techniques. This study concludes that the self-regulation-based LKPD is feasible and practical for use as a supporting tool for character building and independent learning in elementary schools.